(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: Description of knowledge of using metered dose inhalers of parents with bronchial asthma at Thanh Hoa Children’s Hospital in 2025. Methods: Cross-sectional descriptive study with non-probability convenience sampling method, pre-designed instrument set. Results: 72.5% of young parents understood the effects of Ventoline as a reliever inhaler. 91.7% of parents knew when to use a preventative inhaler and 70.8% of parents knew that they should always carry the medicine with them for their children. 74.2% of young parents had correct knowledge about how long to keep the mask closed during one inhalation and 88.3% of parents knew how to clean and dry the spacer. Knowledge of compliance with the procedure of spraying medicine through the spacer reached the highest level in the step of inserting the medicine bottle into the spacer at 99.1% and the lowest level in the step of keeping the mask closed at 75.9%. For the procedure of direct spraying medicine, only 62.5% of parents had the correct knowledge in instructing children to hold their breath for 10-15 seconds. Conclusion: Knowledge of using metered dose inhalers of young parents was relatively good with 26.7% of parents having good knowledge, 62.5% having fair knowledge and 16.7% of parents having average knowledge.